Validation Study of a Korean Version of the Abbreviated University of California, Los Angeles, PTSD Reaction Index (Abb-UCLA-PTSD RI) for Adolescents - Kim, Tae Ho; Han, Doug Hyun; Yoo, Seo Koo; Lee, Jung Jae; Kim, Ji Eun; Chung, Un Sun (Journal of Korean medical science, 2018)
We aimed to verify a Korean version of the Abbreviated University of California, Los Angeles, Post-Traumatic Stress Disorder Reaction Index (Abb-UCLA-PTSD RI-Korean version) among Korean adolescents to assess post-traumatic stress in this population. We recruited 1,254 adolescents who completed the Abb-UCLA-PTSD RI-Korean version scale, the Child Report of Post-Traumatic Symptoms (CROPS), the Lifetime Incidence of Traumatic Events (LITE), and the Children's Depression Inventory (CDI). Test-retest reliability was computed for a randomly selected 314 participants. Among all the students, 765 were included in the analysis because 143 students were classified in the normative group (LITE 1) and 622 were in the traumatized group (LITE 4). The internal consistencies of the nine-item and eight-item versions of the Abb-UCLA PTSD RI-Korean version were found to be high (Cronbach's α = 0.843 and 0.842, respectively). The criterion-related validity was based on comparison of the Abb-UCLA PTSD RI total scores between the normative and trauma groups. For the eight-item version, the normative group (4.6 ± 4.6) and the traumatized group (8.8 ± 6.0) demonstrated better criterion-related validity than those in the nine-item version (4.5 ± 4.3 and 8.5 ± 5.0, respectively). The test-retest reliability of the eight-item version was better than the nine-item version (r = 0.85 vs. 0.77). A two-factor model with eight items (two items regarding sleep, and the other six items made up the second factor) showed the best fit. Our results indicate that the eight-item Abb-UCLA PTSD RI-Korean version is a useful screening tool for post-traumatic stress in Korean adolescents.